Vos Viewer and Publish or Perish: Instruction and assistance in using both applications to enable the development of research mapping - Triono Triono; Rani Darmayanti; Nopa Dwi Saputra (Jurnal Dedikasi, 2023)
Research is the responsibility of students, instructors, and researchers to develop academic publication and community service skills. The caliber of education provided by an institution, faculty, or study program is influenced by research. There are many similarities in terms of research variables and research titles, as well as the frequency with which the phenomenon occurs in contemporary research writing. This makes the investigation appear monotonous and colorless. This happens because when selecting a research title, references from prior research are used without regard to the research title's frequency. Students, professors, and researchers must conduct research mapping based on published articles for students to determine which variables can serve as research topics. This selection seeks to acquire originality in similar research topics. The Publish or Peris application and VOS Viewer can be used to map research journal articles more efficiently.